Application of Geographically Weighted Regression for Vulnerable Area Mapping of Leptospirosis in Bantul District - Prima Widayani; Totok Gunawan; Projo Danoedoro; Sugeng Juwono Mardihusodo (Indonesian Journal of Geography, 2016)
Abstract Geographically Weighted Regression (GWR) is regression model that developed for data modeling with continuous respond variable and considering the spatial or location aspect. Leptospirosis case happened in some regions in Indonesia, including in Bantul District, Special Region of Yogyakarta. The purpose of this study are to determine local and global variable in making vulnerable area model of Leptospirosis disease, determine the best type of weighting function and make vulnerable area map of Leptospirosis. Alos satelite imagery as primary data to get settlement and paddy fields area. The others variable are the percentage of population’s age, flood risk, and the number of health facility that obtained from secondary data. Determinant variables that affect locally are flood risk, health facility, percentage of age 25-50 years old and the percentage of settlement area. Meanwhile, independent variable that affects globally is the percentage of paddy fields area. Vulnerability map of Leptospirosis disease resulted from the best GWR model which used weighting function Fixed Bisquare. There are 3 vulnerable area of Leptospirosis disease, high vulnerability area located in the middle of Bantul District, meanwhile the medium and low vulnerability area showed clustered pattern in the side of Bantul District. Abstrak Geographically Weighted Regression (GWR) adalah model regresi yang dikembangkan untuk memodelkan data dengan variabel respon yang bersifat kontinu dan mempertimbangkan aspek spasial atau lokasi.  Kejadian Leptospirosis terjadi di beberapa wilayah di Indonesia termasuk di wilayah Kabupaten Bantul Daerah Istimewa Yogyakarta. Tujuan dari penelitian ini adalah menentukan variabel lokal dan global dalam membuat model  kerentanan Leptospirosis dan menentukan jenis fungsi pembobot yang terbaik serta membuat peta kerentanan wilayah Leptospirosis menggunakan aplikasi GWR. Citra Satelit Alos digunakan untuk mendapatkan data penggunaan lahan, yang selanjutnya diturunkan menjadi prosentase luas permukiman dan sawah. Parameter lainya adalah prosentase umur penduduk, resiko banjir dan jumlah fasilitas kesehatan yang diperoleh dari data sekunder. Variabel yang berpengaruh secara lokal adalah  Risiko Banjir, Fasilitas Kesehatan Presentase Usia 25-50 tahun, Prosentase Luas Pemukiman, sedangkan variabel independen yang bepengaruh secara global adalah Presentase Luas Sawah.  Peta kerentanan Leptospirosis yang dihasilkan dari model GWR terbaik yaitu menggunakan fungsi pembobot  Fixed Bisquare. Terdapat 3 kelas kerentanan Leptospirosis yaitu kelas kerentanan tinggi berada di desa-desa di tengah Kabupaten Bantul, sedangkan kelas sedang dan rendah menunjukkan pola menggelompok di wilayah pinggiran Kabupaten Bantul